Diabetes secrets - McDermott, Michael T.; Trujillo, Jennifer M. (Philadelphia, PA : Elsevier, 2022)
For more than 30 years, the highly regarded Secrets Series. has provided students and practitioners in all areas of health care with concise, focused, and engaging resources for quick reference and exam review. Diabetes Secrets, features the Secrets' popular question-and-answer format that also includes lists, tables, pearls, memory aids, and an easy-to-read style . making inquiry, reference, and review quick, easy, and enjoyable-
Preceded by Diabetes secrets
Includes bibliographical references and index.
Keywords: Diabetes